EARLY GROWTH AND SURVIVAL OF SOME EUCALYPTS AND AUSTRALIAN TREE SPECIES PLANTED AT TUNG KULA RONGHAI DEVELOPMENT PROJECT IN NORTHEASTERN THAILAND - Boland, D.J.; Pinyopusarerk, K. (วารสารวนศาสตร์ไทย, 2022)
A field trial of Australian tree species was assessed for height and survival at six months and height, diameter at ground level and survival at twelve months after planting. The trial was established in 1986 at Tung Kula Ronghai re-afforestation project as a collaborative effort between the Royal Forest Department (RED) and the Australian Centre for International Agricultural Research (ACIAR). Results to date indicate the importance attached to Eucalyptus camaldulensis by the Royal Forest Department. Nevertheless the results presented here clearly indicate the potential use of several other lesser-known, but promising fast-growing eucalypts (E. tereticornis and E. houseana), acacias (e.g. A. auriculiformis A. difficilis, A. cincinnata, A. holosericea, A. leptocarpa, and A. plectocarpa), and melaleucas (M. bracteata, M. cajuputi, M. leucadendra and M. stenostachya). The trial is still too young to make accurate future predications.